Optimalisasi strategi penjualan komoditi komersial di perum bulog kancab lebak menggunakan Metode AHP dan Analisis SWOT - Butarbutar, Florida; Azizi , Muhamad Dirgari; Hadi, Syarif Hadiwijaya; Assidiq, Muhammad Nurhasan (Jurnal Teknik Industri Terintegrasi (JUTIN), 2025)
Perum Bulog Lebak Branch Office has experienced a decline in commercial commodity sales over the past three years, due to the company's position in quadrant II of the SWOT matrix, where there are internal strengths but faced with external threats. The study aims to calculate the need for commercial rice stocks to achieve the 2023 sales target, analyze the company's position in the SWOT matrix, and determine new strategies to increase sales. The methods used include forecasting with Exponential Smoothing With Trend, which estimates stock needs of 1,121.5 tons and a sales target of 168 billion rupiah. The results of the study show that collaboration with large companies as suppliers is an effective strategy, which has succeeded in increasing sales from 26 billion per month to 43 billion per month, an increase of 40%. The main recommendation is to continue this collaboration to further improve sales performance.